HAKIKAT HERIDITAS, LINGKUNGAN, KEBEBASAN MANUSIA, DAN HIDAYAH TUHAN DALAM PEMBENTUKAN KEPRIBADIAN MANUSIA - Syaiful Dinata (Kanz Philosophia: A Journal for Islamic Philosophy and Mysticism, 2022)
The purpose of this study is to determine the formation of human personality. In this study using the library research method, namely research analyzing written literature in the form of books and scientific journals as the main source. The results of this study indicate that the formation of the human personality, namely heridity and the environment, freedom in the sense, humans cannot be dictated, if humans are dictated then it is already said to be no longer free. What is equally known is that only humans have more freedom than other living beings, so this will certainly have an impact on human personality. Heridity and a good environment may be defeated by human free will, so that it is not a good personality that is created, but a bad personality, and vice versa on the principle of freedom in human will. However, these three factors are framed or can be said to be tied to guidance from God. Therefore, it is undeniable that it is God's guidance that will determine the personality of humans themselves. Then, the factors for the formation of the human personality, namely heredity and the environment, have been recognized in Islam, but these two factors do not run like an object that falls from a tree without any obstacles or disturbances, but in the formation of the human personality sometimes these two factors do not work together. significant. That is, in addition to the two factors that have been recognized in Islam, when these two factors do not play a role, it means that there are other factors that can be said to be quite important in shaping the human personality itself, namely God's guidance.